ANALISA STAKEHOLDER DALAM PENYELENGGARAAN LAYANAN TERPADU SATU ATAP BAGI PEKERJA MIGRAN INDONESIA - Charly Tri Prasetyawan; Bambang Supriyono; I Gede Putra Sri Sentanu (Jurnal Administrasi Publik, 2022)
The problems of Indonesian Migrant Workers are very complex. Some Indonesian people who work abroad face problems in the placement country. To protect migrants, the Indonesian government gives protection during the placement process. This effort is manifested in the form of One-Stop Integrated Services which collaborates various agencies in one place so the community can receive the services easier. The purpose of this study is to identify and analyze the roles of all agencies which give services in Tulungagung's One-Stop Integrated Services. The results show that the stakeholders in the provision of services for migrant workers in Tulungagung's One-Stop Integrated Services consist of policy creators, coordinators, facilitators, implementers, and accelerators. Tulungagung Manpower and Transmigration Office has multiple roles as coordinator, facilitator, and implementer. The difference in output causes the role of the implementer to be divided into mandatory implementer and optional implementer.